Study on the machinability of 316L stainless steel using flame assisted machining - Alkali, A.U. (Asian Research Publishing Network, 2016)
Flame assisted machining is a promising machining process targeted at improving the machinability of difficult to cut materials. Oxyacetylene flame as a heating mechanism is dominantly applied in heat assisted machining with single point turning tools. Investigations with end milling cutters which have a wider cutting area were not explored. Even so, with this approach, previous investigations have notably predisposed interest on machinability end result. As a result, varying machinability improvements have been reported by adopting same approach. However, investigation of the heat source parameters and their influence on the machinability factors were not reported in the wide published literatures. In this work, mathematical model of the flame spot diameter as heat source factor responsible for influencing machinability outcome was obtained. An optimal spot diameter was developed to reconcile the heat source from oxyacetylene flame for application with 40mm diameter end mill tool holder fitted with honed edge insert. Heat source parameters namely focus height, oxygen pressure, acetylene pressure and resident time (FOAR) are investigated as the independent variables responsible for varying spot diameter utilizing Analysis of variance (ANOVA). A response surface methodology was used for the design and finding the optimum flame spot size which will yield minimum heat affected area and superior machinability improvement. The established empirical model suggested that flame spot diameter is influenced by focus height, oxygen gas pressure, acetylene gas pressure and resident time in the same order. It was found that catastrophic wear transpired towards the end of the tool life criterion for several test conditions during dry machining at room temperature. Flame assisted machining was evidently discovered to increase the tool life of uncoated WC - CO end mill insert. With flame assisted machining, surface finish has increased by 80 when the cutting speed was purposely changed from 79 to 125 m/min. Â© 2006-2016 Asian Research Publishing Network (ARPN).